Optical and Electrical Based Indoor Landslide Early Warning System Based on the Change of the Wall Crack Width - Marzuki, Ahmad; Purnomo, F. A.; Yoeseph, N. M.; Imran, A. M.; Suryanto, W.; Juhana, T. (IOP Conference Series: Earth and Environmental Science, 2022)
Wall Cracks in a slope area with high landslide risk is very common. Triggered by small horizontal land movement, relative movement of walls separated by the crack line to create wider crack can occur. In the present work, an early warning system for landslide utilizing such movement is presented. For this purpose, a bar is connected to the displacement sensor. Sensor is fixed to one side of wall at either before or after crack line. The bar from this sensor is fixed to the other side of the wall at the direction perpendicular to the crack. With this configuration, small movement of one part of wall (before or after crack line) activate the sensor. In this paper, two displacement sensors are used, i.e., displacement sensor based on slide resistor and fiber sensor. In the present work, warning is given in the form of sound characterized the increase of frequency as the width of crack increase.